Alternative Dosing Regimens of Tislelizumab Using a Pharmacometrics Model‐Based Approach - Ahsan Rizwan; Hugh Giovinazzo; Tian Yu; Yuying Gao; Kun Wang; Fengyan Xu; Ya Wan; Jun Wang; Srikumar Sahasranaman; Marcia Campbell; Patrick Schnell; Ramil Abdrashitov; et al. (Clinical and Translational Science)
ABSTRACT Tislelizumab 200 mg once every 3 weeks (Q3W) is approved for the treatment of multiple cancers. We used a model‐based approach to propose three alternative dosing regimens, 150 mg Q2W, 300 mg Q4W, and 400 mg Q6W, with the aims of providing flexible treatment regimens compatible with background chemotherapy and/or reducing infusion visits. A previously developed population pharmacokinetic model was used to simulate pharmacokinetic exposure of the alternative regimens. Regulatory guidance on alternative dosing was used to define pharmacokinetics‐based criteria. Alternative doses were selected by simulation, exposure matching, and comparison to the reference regimen of 200 mg Q3W. Deviations from pharmacokinetics‐based criteria were bridged using appropriate safety and efficacy references and exposure–response analyses. All three alternative dosing regimens produced comparable exposures versus 200 mg Q3W. Although simulated peak serum concentration (Cmax) at 300 mg Q4W and 400 mg Q6W was higher versus 200 mg Q3W, this was below the Cmax of the 5 mg/kg Q3W safety reference. And while the trough serum concentration (Ctrough) for 400 mg Q6W was slightly lower versus 200 mg Q3W, it was 10.7% higher than the 2 mg/kg efficacy reference Ctrough, and therefore, within the concentration range in which a flat exposure–efficacy relationship of tislelizumab has been established. Tislelizumab regimens of 150 mg Q2W, 300 mg Q4W, and 400 mg Q6W are expected to result in similar safety and efficacy as 200 mg Q3W.